Economic base multipliers: a comparison of ACDS and IMPLAN. Issue 3 (16th May 2013) - Mulligan, Gordon; Jackson, Randall; Krugh, Amanda
Abstract Many local and regional practitioners still use the single multiplier version of economic (export) base analysis in project assessments. However, dependable estimates of this multiplier require that the division of total activity into its export (basic) and local (non‐basic) components be reasonably accurate across all industries. This paper compares the economic base multiplier that is generated by a shortcut approach, one calibrated by the Arizona Community Data Set (ACDS), with that generated by the popular IMPLAN input‐output model. The comparison is made across 577 micropolitan (all non‐metropolitan) US counties in the year 2000. Although the two approaches are not at all similar they generate comparable economic base multipliers. Moreover, various regional attributes, like human capital and specialization, affect the two multiplier estimates in much the same way.